Hepatobiliary organoid research: the progress and applications - Zou, Rui-Qi; Dai, Yu-Shi; Liu, Fei; Yang, Si-Qi; Hu, Hai-Jie; Li, Fu-Yu (Frontiers in Pharmacology, 2025)
Organoid culture has emerged as a forefront technology in the life sciences field. As “in vitro micro-organs”, organoids can faithfully recapitulate the organogenesis process, and conserve the key structure, physiological function and pathological state of the original tissue or organ. Consequently, it is widely used in basic and clinical studies, becoming important preclinical models for studying diseases and developing therapies. Here, we introduced the definition and advantages of organoids and described the development and advances in hepatobiliary organoids research. We focus on applying hepatobiliary organoids in benign and malignant diseases of the liver and biliary tract, drug research, and regenerative medicine to provide valuable reference information for the application of hepatobiliary organoids. Despite advances in research and treatment, hepatobiliary diseases including carcinoma, viral hepatitis, fatty liver and bile duct defects have still been conundrums of the hepatobiliary field. It is necessary and crucial to study disease mechanisms, establish efficient and accurate research models and find effective treatment strategies. The organoid culture technology shed new light on solving these issues. However, the technology is not yet mature, and many hurdles still exist that need to be overcome. The combination with new technologies such as CRISPR-HOT, organ-on-a-chip may inject new vitality into future development.